FUS is Phosphorylated by DNA-PK and Accumulates in the Cytoplasm after DNA Damage - Deng, Qiudong (Society for Neuroscience, 2014)
Abnormal cytoplasmic accumulation of Fused in Sarcoma (FUS) in neurons defines subtypes of amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). FUS is a member of the FET protein family that includes Ewing's sarcoma (EWS) and TATA-binding protein-associated factor 2N (TAF15). FET proteins are predominantly localized to the nucleus, where they bind RNA and DNA to modulate transcription, mRNA splicing, and DNA repair. In ALS cases with FUS inclusions (ALS-FUS), mutations in the FUS gene cause disease, whereas FTLD cases with FUS inclusions (FTLD-FUS) do not harbor FUS mutations. Notably, in FTLD-FUS, all FET proteins accumulate with their nuclear import receptor Transportin 1 (TRN1), in contrast ALS-FUS inclusions are exclusively positive for FUS. In the present study, we show that induction of DNA damage replicates several pathologic hallmarks of FTLD-FUS in immortalized human cells and primary human neurons and astrocytes. Treatment with the antibiotic calicheamicin γ1, which causes DNA double-strand breaks, leads to the cytoplasmic accumulation of FUS, TAF15, EWS, and TRN1. Moreover, cytoplasmic translocation of FUS is mediated by phosphorylation of its N terminus by the DNA-dependent protein kinase. Finally, we observed elevated levels of phospho-H2AX in FTLD-FUS brains, indicating that DNA damage occurs in patients. Together, our data reveal a novel regulatory mechanism for FUS localization in cells and suggest that DNA damage may contribute to the accumulation of FET proteins observed in human FTLD-FUS cases, but not in ALS-FUS.